Writing and Research in the Philippines: Comparative Notes - Garcia, J. Neil C. (Kasarinlan: Philippine Journal of Third World Studies, 2015)
Opening remarks of Dr. J. Neil C. Garcia, director of the UP Press, for the 2014 TWSC Writeshop.